Information technologies in environmental engineering new trends and challenges - Golińska, Paulina; Fertsch, Marek; Gómez, Jorge Marx (Environmental Science and Engineering, 2011)
This monograph contains recent studies in eco-informatics, promising ideas and new challenges in information management for supporting sustainability in companies and other organization. The scope of this book includes sets of solutions which show different stakeholders? viewpoints on sustainability. In individual chapters, authors discuss the role which Environmental Information Systems (EIS) play in the environmental conscious functioning of enterprise. New models, methods and tools supporting sustainability are presented. Emphasis is placed on the innovative approach to eco-friendly organization and coordination of transport, logistics processes and operations management. The information management and decision making in manufacturing and service organizations is highlighted. The scope of this monograph also encompasses topics related to the modeling and monitoring of climate change.